Effect of Heating at Various Temperatures for 30 Minutes on Pathogenicity of White Spot Syndrome Virus (WSSV) in Tiger Prawn (Penaeus monodon Fabr.) - Priatni, D.; Alifuddin, M.; Djokosetiyanto, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
White spot syndrome virus (WSSV) is a strong pathogenic virus which spread very rapidly and can cause tiger shrimp mass mortality within a short period. Enhancement of shrimp immunity by infecting inactivated WSSV is one of the efforts to overcome WSSV infection in shrimp. In this study, inactivated WSSV were prepared by heating them with various temperatures namely 45, 50, 55 and 60oC for 30 minutes. The results shows that infection with heating inactivated WSSV at 45°C and 60°C for 30 min on PL-15 could increase their immunities. The survival rate of inactivated WSSV-infected shrimp after challenge test with WSSV virulent reached 77%, while no survive shrimp was observed in control. This suggests that shrimp immunity could be improved by vaccination using WSSV virus inactivated by heating. Keywords: WSSV virus, pathogen, tiger shrimp, heating ABSTRAK White Spot Syndrome Virus (WSSV) merupakan virus yang sangat ganas bagi udang windu, dengan penularan yang sangat cepat dan menyebabkan kematian dalam waktu yang cepat. Peningkatan imunitas udang dengan meenginfeksikan WSSV inaktif merupakan salah satu upaya untuk menanggulangi infeksi WSSV pada udang. Pada penelitian ini, inaktivasi WSSV dilakukan menggunakan pemanasan pada suhu berbeda, yaitu 45, 50, 55 dan 60oC selama 30 menit. Hasil penelitian menunjukkan bahwa infeksi PL-15 menggunakan virus WSSV yang telah diinaktivasi dengan pemanasan pada suhu 45oC dan 60oC dapat meningkatkan daya tahan udang. Kelangsungan hidup udang yang telah diinfeksi dengan WSSV hasil inaktivasi sebelum uji tantang dengan WSSV virulen mencapai 77%, sementara udang yang tidak diinfeksi dengan WSSV hasil inaktivasi adalah semua mati. Dengan demikian dapat disimpulkan bahwa daya tahan udang dapat ditingkatkan melalui vaksinasi menggunakan WSSV yang telah diinaktivasi dengan pemanasan. Kata kunci: virus WSSV, patogen, udang windu, pemanasan